The Effect of Discovery Learning on Students’ Conceptual Understanding of Cell - Komariah, Siti; Jayanti, Ummi Nur Afinni Dwi (FKIP Universitas Lampung, 2022)
This study aims to determine the effect of discovery learning on cell material on students' concept comprehension of class XI. In this study, the quantitative research method used quasi-experiments and a non-equivalent pretest-posttest control group design. The instruments used in the research consisted of learning materials (lesson plan, students’ worksheet and textbooks) and data collection instruments in the form of reasoned multiple choice written tests of 20 pretest-posttest questions. The research was conducted at Madrasah Aliyah Batu Bara. The population in this study were all 3 classes of XI IPA, and the sample used was 2 classes totaling 60 students taken using cluster random sampling technique. Class XI IPA 1 as an experimental class using the discovery learning model, while class XI IPA 2 as a control class using conventional learning methods. Data analysis techniques in this study were analyzed using ANCOVA. The results showed that there was an influence of the discovery learning model on cell material on students' concept comprehension. Keywords: conceptual understanding, discovery learning model, biology lesson. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1900-1915